BONE MARROW UPTAKE IN PARATHYROID SCINTIGRAPHY IS A CONSEQUENCE OF EXTREMELY HIGH PARATHYROID HORMONE LEVELS - Koc, Zehra Pinar; Balci, Tansel Ansal; Dogukan, Ayhan (Amer Assoc Clinical Endocrinologists, 2013)
Objective: We retrospectively evaluated patients with end-stage renal disease (ESRD) who were referred to our department for parathyroid scintigraphy. The aim of this study was to investigate the causes of bone marrow uptake observed on parathyroid scintigraphy. Methods: We included 18 ESRD patients (10 F, 8 M; mean, 52 +/- 13 years old; range, 45-59) in the study. The disease duration of the patients was mean 7.7 +/- 4.7 years. The patients' mean plasma calcium and parathormone (PTH) levels were 9.7 +/- 1.4 mg/dL and 1,553.3 +/- 691.7 pg/mL, respectively. Dual-phase technetium-99m 2-methoxyisobutyl-isonitrile (Tc-99m MIBI) parathyroid imaging and, if necessary, additional Tc-99m pertechnetate scintigraphy were performed. Quantification of the planar early phase parathyroid images was performed for various regions (sternum, humerus, ribs) with the same size rectangular region of interest (ROI, 176 x 176 pixels). Average counts were compared with paired samples Student's t tests, and P<.05 was considered statistically significant. Results: Tc-99m MIBI parathyroid imaging revealed parathyroid hyperplasia, adenoma, and ectopic adenoma in 7, 3, and 2 patients, respectively. The other 7 patients had normal scintigraphy results with regard to parathyroid pathologies. Bone marrow uptake in the sternum, ribs, and humerus was observed in 6 patients. The difference between the average quantitative value obtained from the ROIs drawn on the sternum and humerus was also statistically significant compared to patients without bone marrow uptake (P<.05). All 6 patients' exhibited extremely high PTH levels (>2,000 pg/mL; mean, 2,413.7 +/- 150 pg/mL) compared to the other 12 patients (mean, 1,342.8 +/- 249 pg/mL). Conclusion: Our results show that bone marrow uptake on parathyroid scintigraphy is a consequence of extremely high PTH levels in ESRD patients; no further analysis is required.
Keywords: Multiple-Myeloma; Primary Hyperparathyroidism; Localization; Tl-201